2017
DOI: 10.1016/j.chembiol.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal Anti-inflammatory Drugs Are Caspase Inhibitors

Abstract: Summary Non-steroidal anti-inflammatory drugs (NSAIDs) are among the most commonly used drugs in the world. While the role of NSAIDs as cyclooxygenase (COX) inhibitors is well established, other targets may contribute to anti-inflammation. Here we report caspases as a new pharmacological target for NSAID-family drugs such as ibuprofen, naproxen, and ketorolac at physiologic concentrations both in vitro and in vivo. We characterize caspase activity both in vitro and in cell culture, and combine computational mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 63 publications
2
60
1
Order By: Relevance
“…It is interesting to note that 3 out of the 4 FDA compounds capable of inhibiting caspase-3 activity, namely diflunisal, pranoprofen, and fenoprofen, are NSAIDs. We also observed other NSAIDs among the top 100 hits from our virtual screening, such as fenbufen (allosteric site rank: 11, orthosteric site rank: 76), and flufenamic acid (78, 272) which have been shown to have anti-caspase activity by Smith et al 29 but suggested that the NSAIDs could bind to the orthosteric S1 subsite. In…”
Section: Nsaids As Caspase Inhibitorssupporting
confidence: 55%
See 1 more Smart Citation
“…It is interesting to note that 3 out of the 4 FDA compounds capable of inhibiting caspase-3 activity, namely diflunisal, pranoprofen, and fenoprofen, are NSAIDs. We also observed other NSAIDs among the top 100 hits from our virtual screening, such as fenbufen (allosteric site rank: 11, orthosteric site rank: 76), and flufenamic acid (78, 272) which have been shown to have anti-caspase activity by Smith et al 29 but suggested that the NSAIDs could bind to the orthosteric S1 subsite. In…”
Section: Nsaids As Caspase Inhibitorssupporting
confidence: 55%
“…Since previous studies have ruled out the possibility of non-steroidal anti-inflammatory drugs (NSAIDs) inhibiting the activity of luciferase, we did not perform further studies on that prospect. 29 Initial screening was performed using 50 μM concentration of each compound and tested against caspase-3 enzyme activity. Diflunisal and pranoprofen showed maximal inhibition when compared with fenoprofen and flubendazole.…”
Section: Inhibition Studies On Recombinant Human Caspase-3 Enzymementioning
confidence: 99%
“…In other cases such molecules are competitive inhibitors of caspase substrates, which prevent apoptotic-dependent tissue damage [104] . Caspase inhibitors have also been used to regulate the inflammatory response [105] and treat specific diseases [106] , [107] . However the inclusion of these molecules into the clinic has proven challenging [108] , [109] , [110] .…”
Section: Therapeutic Potential Of Caspase Modulation In Stem Cellsmentioning
confidence: 99%
“…Apart from the intended target, small molecules often have off-target effects on other proteins or processes. While these effects can confound the interpretation of large-scale studies, careful analysis can pinpoint unexpected mechanisms of action and new drug repurposing opportunities 12,[15][16][17][18] . Most largescale drug repurposing studies focus on protein off-targets, but compoundspecific chemical reactivities that can contribute to unanticipated biological effects within the cell, independent of protein engagement, are often ignored 19 .…”
mentioning
confidence: 99%